2007
DOI: 10.1590/s1413-70542007000600018
|View full text |Cite
|
Sign up to set email alerts
|

Produção da batata-doce adubada com esterco bovino e biofertilizante

Abstract: RESUMOObjetivou-se avaliar a produção da batata-doce (Ipomoea batatas (L.) Lam.) adubada com esterco bovino e biofertilizante, conduziu-se um experimento no período de Janeiro a Junho de 2004, em NEOSSOLO REGOLÍTICO, psamítico típico, na Universidade Federal da Paraíba, em Areia-PB. O delineamento experimental empregado foi de blocos casualisados, com quatro repetições com os tratamentos distribuídos em arranjo fatorial 6 x 2, sendo seis doses de esterco bovino (0, 10, 20, 30, 40, 50 t ha -1 ) e ausência e pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
12

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 2 publications
0
4
0
12
Order By: Relevance
“…Lagoa Seca, EMEPA, 2007. in comparison to its application to the plant leaves (Figures 2 and 3). However, Oliveira et al (2007) obtained productivity of 12.9 t ha -1 of commercial roots of sweet potato with the utilization of cattle manure and a concentration of 20% of biofertilizer. On the other hand, Barbosa (2005) produced 13.4 t ha -1 of commercial sweet potato roots with the application of biofertilizer at the concentration of 20%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lagoa Seca, EMEPA, 2007. in comparison to its application to the plant leaves (Figures 2 and 3). However, Oliveira et al (2007) obtained productivity of 12.9 t ha -1 of commercial roots of sweet potato with the utilization of cattle manure and a concentration of 20% of biofertilizer. On the other hand, Barbosa (2005) produced 13.4 t ha -1 of commercial sweet potato roots with the application of biofertilizer at the concentration of 20%.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, Soares et al (2002) and Santos et al (2006) reported that cattle manure application improved the production of tuber roots. Furthermore, Oliveira et al (2007) reported improvement of tuber roots productivity with the application of biofertilizers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Santos et al (2006) alcançaram aumentos na produtividade total e comercial de raízes batata-doce com o uso de matéria orgânica no solo, respectivamente. Oliveira et al (2007b), obtiveram produtividade de 20 e 17,01 t ha -1 de batata-doce, em função das doses de esterco bovino na presença do biofertilizante, aplicado na folha e no solo, respectivamente.…”
Section: Introductionunclassified
“…The effects of manure application have also been analyzed by other authors (Scherer et al, 2006;Oliveira et al, 2007), showing a significant increase in productivity through a quadratic effect, except at the highest doses. Machado et al (1983) also observed the effect of cattle manure with the application of 20 t ha -1 , where the yields of two harvests of irrigated rice (Oryza sativa) were similar to those of control plants.…”
Section: Resultsmentioning
confidence: 87%